Ethanol-Induced Changes in PKCε: From Cell to Behavior - Pakri Mohamed, Rashidi M.; Mokhtar, Mohd H.; Yap, Ernie; Hanim, Athirah; Abdul Wahab, Norhazlina; Jaffar, Farah H. F.; Kumar, Jaya (Frontiers in Neuroscience, 2018)
Long-term binge ethanol intake causes neuroadaptive changes where drinkers require more than the usual amount to experience the effects of ethanol. This neuroadaptation is partly due to modulation of numerous neurotransmitter receptors by protein kinase Cs (PKCs). PKCs are enzymes that control cellular activities by regulating other proteins through phosphorylation. Among the various isoforms of PKC, PKCε is most implicated in ethanol-induced biochemical and behavioral changes. Ethanol exposure causes changes to the expression and localization of PKCε in various brain regions that mediate addiction-favoring plasticity. Ethanol works in conjunction with numerous upstream kinases and second messenger activators to affect cellular expression of PKCε. Chauffeur proteins such as receptors for activated C kinase (RACK) translocate PKCε to aberrant sites and mediate ethanol-induced changes. In this article, we aim to review the following: the general structure and function of PKCε, ethanol-induced changes in expression of PKCε, regulation of ethanol-induced PKCε activities in DAG-dependent and –independent environment, mechanisms underlying PKCε-RACKε translocation in the presence of ethanol, and existing literature on the role PKCε in ethanol-induced neurobehavioral changes and synthesize a working model upon which further research can build on.